Immunology & serology in laboratory medicine - Turgeon, Mary Louise (Elsevier/Mosby, 2014)
This classic resource offers the current, comprehensive coverage of immunology you need to stay on the cutting-edge of clinical laboratory science. It provides a solid foundation of knowledge and skills to take you from basic immunologic mechanisms and serologic concepts to the theory behind the procedures you'll perform in the lab, including automated techniques. It also explores the medical applications of clinical laboratory science, with information on disorders of infectious and immunologic origin, as well as topics such as transplantation and tumor immunology. Learning objectives, review questions, step-by-step procedures, and case studies help you master key concepts and prepare you to succeed in today's modern laboratory environment.